Eksplorasi Joyful Learning dalam Perspektif Teori Humanistik di SDIT Al-Jamiel Palangka Raya - Lutfi, Saiful; Mazrur, Mazrur; Saihu, Made (Jayapangus Press, 2025)
Effective education requires a holistic approach, which not only focuses on cognitive aspects, but also considers the emotional and contextual aspects for students. This study aims to analyses the implementation of various strategies in creating fun and meaningful learning experiences at the primary school level, focusing on the use of interactive and creative learning methods, providing positive reinforcement, and connecting learning materials with students' daily lives. The methods used in this research are interviews, observations, and quantitative data analysis through surveys to teachers, students, and parents. The results show that using interactive and creative methods can increase student engagement, while providing positive reinforcement can reinforce desired learning behaviors. In addition, connecting learning to student’s daily lives is proven to significantly improve students’ understanding and interest in learning. As many as 80% of teachers stated that linking subject matter to real situations around students increases the attractiveness of the material, while 70% of students claimed to be more interested in learning that is relevant to their lives. This research provides important insights into the importance of humanistic and contextualized approaches in primary education to create a more enjoyable and effective learning experience.